2015
DOI: 10.1016/j.jsha.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and evolutionary characteristics of heart failure in patients with left bundle branch block – A Moroccan center-based study

Abstract: Our analysis emphasizes increased in-hospital mortality and higher disease severity, over a short period of stay, in heart failure patients with left bundle branch block.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…The patients had an average disease duration of 8 ± 2.74 years, and more men than women were affected. A study of the development of heart failure among subjects with left bundle branch block showed that these subjects have a high prevalence of idiopathic dilated cardiomyopathy compared to other forms (39.1% vs. 4.8% p < 0.001), with a high frequency of hospitalization for heart failure (64.5% vs. 23.3%, p < 0.001), and that left ventricular ejection fraction was significantly lower in this group [ 12 ]. Myocardial infraction was studied in the Fes [ 13 ] and Rabat region [ 14 ], with results indicating a high percentage among men (aged 58 years and older), 51% in the Fes and 57.28% in the Rabat region, with smoking as the dominant risk factor.…”
Section: Resultsmentioning
confidence: 99%
“…The patients had an average disease duration of 8 ± 2.74 years, and more men than women were affected. A study of the development of heart failure among subjects with left bundle branch block showed that these subjects have a high prevalence of idiopathic dilated cardiomyopathy compared to other forms (39.1% vs. 4.8% p < 0.001), with a high frequency of hospitalization for heart failure (64.5% vs. 23.3%, p < 0.001), and that left ventricular ejection fraction was significantly lower in this group [ 12 ]. Myocardial infraction was studied in the Fes [ 13 ] and Rabat region [ 14 ], with results indicating a high percentage among men (aged 58 years and older), 51% in the Fes and 57.28% in the Rabat region, with smoking as the dominant risk factor.…”
Section: Resultsmentioning
confidence: 99%
“…Further risk factors include hypertension, hyperlipidemia, smoking cigarettes, and male gender [ 1 , 4 ]. While diabetes mellitus (DM) is considered a protective factor or an independent factor in most reported cases, in Saudi Arabia, one study found that DM was associated with many CAE patients [ 4 , 8 ]. Other etiologies can contribute to the development of CAE such as vasculatides (Kawasaki disease, polyarteritis nodosa), connective tissue diseases (rheumatoid arthritis, systemic lupus erythematous, scleroderma), Marfan syndrome, and iatrogenic causes (stenting, angioplasty, coronary atherectomy) [ 4 - 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The usual sequences of conduction changes dramatically in LBBB, which results in specific image on the ECG (1). The left bundle branch receives its primary blood supply from the LAD, particularly in the first segment while to the right bundle branch, the right and circumflex coronary arteries may supply some collateral flow (2). As for right bundle, conduction in the left bundle can be compromised by both structural and functional factors.…”
Section: Introductionmentioning
confidence: 99%
“…As such, various chronic diseases which causes fibrotic disease (e.g., hypertension, coronary myocardial cardiomyopathies can cause LBBB (1). LBBB may occur after acute coronary syndrome such as MI, or myocarditis and in such conditions is usually associated with a worse prognosis (2).…”
Section: Introductionmentioning
confidence: 99%